By Mastering English Vocabulary Can Increase the Learning Quality of Reading Comprehension Narrative Text on X MMA and X MMB at SMKN 7 Mataram - Ahmad Mursid (DIKSI: Jurnal Kajian Pendidikan dan Sosial, 2022)
The purpose of this study is to find out whether By mastering the students’ English vocabulary and their reading comprehension skills. This research is quantitative research. The population of the research was 49 students of the second grade of SMKN 7 Mataram. There were two classes of the second-grade students of SMKN 7 Mataram. The sample was taken by using simple random sampling and class of X MMA and X MMB was taken as the sample of the research from 38 classes. The aim of reading comprehension skill and vocabulary mastery test were used as the instruments to measure the level of students’ comprehension skill and vocabulary mastery in this research. Based on the result of the tests of 39 students as a sample and by applying the formula of person’ coefficient correlation.  The statistical analysis shows that the correlation coefficient between the students’ vocabulary mastery and their reading comprehension is also significant (p < .01; p = .000). After considering the result, therefore the null hypothesis (H01) is rejected and the alternative hypothesis (H1) is accepted. It can conclude that By mastering English vocabulary and their achievement in reading comprehension. The higher vocabulary mastery had gotten by the students, the higher reading comprehension had gotten by the students. This suggests that from the result of this research mean that teaching vocabulary is a necessity before teaching further reading comprehension skills.